2004
DOI: 10.1111/j.1537-2995.2004.03275.x
|View full text |Cite
|
Sign up to set email alerts
|

Positively charged porphyrins: a new series of photosensitizers for sterilization of RBCs

Abstract: Porphyrin Tri-P(4) may be a suitable photosensitizer for sterilization of RBCs. However, further exploration to optimize the method is necessary to reach clinically acceptable goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 43 publications
0
28
0
1
Order By: Relevance
“…In comparative studies, AS‐3 was shown to prevent postthaw hemolysis better than the ASs EAS‐61 13 and AS‐1 7 . In addition, after certain pathogen inactivation procedures, RBC integrity was better maintained in AS‐3 compared to SAGM 14,15 . The main difference between AS‐3 and the other studied ASs is the presence of high amounts of citrate (22 mmol/L) and phosphate (15.5 mmol/L) in AS‐3.…”
Section: Discussionmentioning
confidence: 96%
“…In comparative studies, AS‐3 was shown to prevent postthaw hemolysis better than the ASs EAS‐61 13 and AS‐1 7 . In addition, after certain pathogen inactivation procedures, RBC integrity was better maintained in AS‐3 compared to SAGM 14,15 . The main difference between AS‐3 and the other studied ASs is the presence of high amounts of citrate (22 mmol/L) and phosphate (15.5 mmol/L) in AS‐3.…”
Section: Discussionmentioning
confidence: 96%
“…We previously reported that it was active in mediating PDI against gram-positive bacteria (44). TriP(4) is a cationic porphyrin that has been reported to be active in mediating PDI against both gram-positive and gram-negative bacteria (27) as well as fungi (43) and viruses (47). The pL-ce6 conjugate is a member of a class of macromolecular conjugates between polycationic polymers and PS that show a high degree of efficiency in mediating PDI of both classes of bacteria in vitro and in vivo (16,18,19).…”
Section: Resultsmentioning
confidence: 99%
“…In order to minimize this risk, the development of new approaches of blood disinfection with drugs targeting a broad range of pathogens should be addressed. The use of porphyrins and its analogs in PDT for viral inactivation of blood products has proved successful (24,25,28,50,51), and VSV is often used as a model virus in such tests (24,25,41). In this context, PPIX, ZnPPIX, and MPIX could be used for blood disinfection as well and should be tested for their cytotoxicity for blood cells.…”
Section: Vesicular Stomatitis Virus Inactivation By Porphyrins Antimimentioning
confidence: 99%